Determining biological value and quality indicators of beverages of the drinkbreakfast type - Dzyuba, Nadya; Telezhenko, Liubov; Kalugina, Iryna; Kozonova, Yuliia; Serdyuk, Marina; Danchenko, Olena; Sukharenko, Elena; Zdorovtseva, Lubov; Hidzhelitskyi, Vitalii (Eastern-European Journal of Enterprise Technologies, 2018)
We have developed formulations and production technology for beverages of the “drinkbreakfast” type with the elevated content of protein and pronounced antioxidant properties. Components of the composition include cottage cheese, nonfat milk, sesame seeds, walnuts, honey, banana, spinach, psyllium, hydrolyzed collagen (glutin). The beverages are the sources of digestible protein, antioxidant vitamins (C, E, PP) and dietary fiber. By introducing glutin into the composition, a single portion of the developed beverages “Spinach” and “Banana” satisfy a need in proteins by 7.6 % and 7.2 %, respectively. The introduction of spinach and banana to the composition promotes their enrichment with folates. An analysis of mineral composition of the developed beverages allows us to argue on that the beverages are the sources of basic macro and micronutrients that satisfy the need in them at a high level. Using psyllium and glutin as active ingredients improves antioxidant activity by 50‒60 times, which is explained by the synergy among all components. We determined the technological conditions for psyllium hydration. It was established that the average size of dry particles of psyllium is 1.79 mm, and that of hydrated is 2.28 mm (5 min, 20 °C). A layer of mucus ‒ soluble food fiber ‒ forms at the particles’ surface, which stabilizes the food system. Using glutin as a foaming agent in the beverages enables the formation of a stable aerated structure. The cell size of foam in the beverage “Spinach” varies in the range 0.05‒0.15 mm, and in the beverage “Banana” ‒ from 0.001 to 0.15 mm. Modeling storage conditions by using the ALST assessment test in terms of change in the microbiological and organoleptic parameters allows us to confirm that the beverages will be competitive in the consumer market of Ukraine. When stored over 36 hours at a temperature of (4±2) °C and at humidity not exceeding 75 % in an airtight container, the content of sanitaryindicative microorganisms complies with the hygienic requirements to milkbased beverages. The developed “drinkbreakfast” beverages could be recommended for children, as well as for the diet of pregnant women, as well as for women in the lactation period